Fertility issues: the perceptions and experiences of young men recently diagnosed and treated for cancer - Chapple, A; Salinas, M; Ziebland, S; McPherson, A; Macfarlane, A (Elsevier, 2007)
Purpose: To explore fertility issues for young men who had been diagnosed and treated for cancer and to examine communication problems surrounding these fertility issues. Method: Narrative interviews were conducted with 21 young men previously treated for cancer in the United Kingdom. Eighteen talked about fertility issues at some length. A qualitative interpretive approach was taken, combining thematic analysis with constant comparison. Results: Communication about sperm storage was sometimes difficult and embarassing. Young men wanted the opportunity to bank their sperm but decisions were often rushed. Some would have appreciated counseling and were unprepared for the process of sperm banking and criticized facilities. Uncertainty about fertility status caused worries for the future. Conclusions: More still needs to be done to help young men with cancer to address issues of fertility. All adolescents and young men treated for cancer should be offered sperm banking if their fertility may be affected. They should be offered counseling at every stage by professionals who feel comfortable talking about the subject. Interactive, educational CD-ROMs or websites may be useful. Physical facilities for sperm banking should be improved.